SAT0585 Evaluation of Wikipedia Rheumatology Articles as A Learning Resource for Medical Students. (10th June 2014) - Antivalle, M.; Battellino, M.; Ditto, M.C.; Varisco, V.; Chevallard, M.; Rigamonti, F.; Batticciotto, A.; Atzeni, F.; Sarzi-Puttini, P.
Abstract : Background: Despite concerns regarding its accuracy and reliability, Wikipedia is increasingly being used by medical students as a source of medical information (1, 2). Objectives: Aim of our study was to evaluate whether Wikipedia rheumatology articles could represent a reliable source of information for medical students. Methods: Our study analyzed articles available on the English Wikipedia database (http://en.wikipedia.org ). From the International Classification of Diseases (ICD-10), 283 rheumatologic codes were identified, mainly but not exclusively from the "diseases of the musculoskeletal system and connective tissue" group (codes M00-M99). Of these, 178 (62.9%) had a separate Wikipedia entry, or an individual paragraph within more general entries. 25 of these entires were labelled as "stubs" – articles containing only one or a few sentences of text, too short to provide encyclopedic coverage of a subject, but capable of expansion-, and were therefore not included in the analysis. The readability of the remaining 153 articles was assessed by the Flesch Reading Ease Score, and the reliability was evaluated by the total number of references and by the date of the last update. Further, 18 main headings of broad rheumatologic interest were selected for in-depth independent examination by 4 blinded assessors (2 rheumatology fellows and 2 experienced consultants). The accuracy and depth of coverage of all selected articles were examined by each assessor using a modified (3) DISCERN instrument (4), with evaluation on a five-level (1 to 5) scale of 21 items covering the validity of article contents. The agreement between assessors was evaluated by intraclass correlation coefficient (ICC). Results: The mean Flesch Reading Ease Score of the entire group of 153 articles was 33.78 (range -17 - 55). 33% of articles had a FRE score <30, a level usually considered appropriate for university graduates. The mean number of references was 22, 83±35.29, range 0 – 258. Wikipedia articles were last updated on average 102 days (range 0 – 1204) before the assessment, 83% of entries having been updated in the last 6 months. For the 18 selected articles, the median score of all 21 considered items was 3.22; average scores between 4.0 and 5.0 were assigned to items related to the transparency of sources, overall article balance, and coverage of topics; scores of items related to treatment options ranged from 1.250 to 2.625; a modest score was assigned to overall completeness of articles (2.625), while the scientific correctness and the appropriateness of information for medical students were rated 3, 875 and 3, 625 respectively. Overall, the 4 assessor showed a satisfactory agreement (ICC 0.839, p=0.000). Conclusions: Our study shows that Wikipedia articles covering rheumatology topics articles are generally up-to-date, contain a reasonable number of cited references, and have an acceptable scientific content. However, the discussion is often incomplete, and important aspects tend to be incompletely addressed. The use of rheumatology articles of Wikipedia as a learning resource for medical students should not be encouraged. References: Med Teach. 2013;35:337. Br J Educ Technol. 2010;42(2)351–360. Eur J Gastroenterol Hepatol 2014;26:155–163. J Epidemiol Community Health 1999;53:105–111. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5610